Nonlinear anticyclone structures in the Earth's atmosphere - Saliuk, D.; Agapitov, O. (Advances in Astronomy and Space Physics, 2011)
We present some results of the study of nonlinear vortex structures in the Earth's atmosphere known as blocking-anticyclones. It is shown that synoptic-scale structure can be considered in the geostrophic approximation in terms of the Charney-Obukhov equation. The numerical scheme based on the full reduction method is proposed to study the dynamics of the initial perturbations. The dominant role of the vector nonlinearity for the vortex structures stability is shown. In the absence of the nonlinearity the vortex structures are unstable and quickly decompose into the linear Rossby waves. The linear and nonlinear anticyclone structures dynamics in the Earth's atmosphere were studied using the data from NCEP(National Centers for Environmental Prediction) / NCAR (National Center for Atmospheric Research) data base - pressure, geopotential, temperature, wind velocity. Blocking anticyclones exist during a long time (typical lifetime is from 5 days to a month), while linear anticyclone exist few days (up to 5 days). Conventional synoptic anticyclone usually moves eastward but blocking anticyclones usually move westward (or stay on the same place in the zonal flow). It was also found that blocking anticyclones have larger amplitude of temperature and pressure perturbations, so the impact of the blocking anticyclone on the formation of weather is larger.